Designing a destination: a plan for the River Market transit station district - Coen, Kris (Kansas State University, 2009)
The location and type of future development around a light rail transit station has the ability to affect its success of failure. Not only should the location of the future light rail line be carefully considered, but the locations of stops will greatly affect future development of the surrounding areas. The implementation of a light rail system has been proposed for downtown Kansas City as a solution to link its many attractions which are currently spread throughout the metro area. Although the proposal has not been passed by voters, the concept has generated a great deal of interest and brought up challenges Kansas City would need to address such as funding, alignment, space requirements and impacts on future development. The success of such a large scale, public project would require significant amounts of coordination and planning between many people. By using the current proposed alignment and studying seven stations located in the core of downtown Kansas City, the station which would require a station district plan the most could be determined. From there, through inventory and analysis of the surrounding area, guidelines would be written to put parameters on future development occurring as a result of light rail implementation. Planning a transit station district in this way would allow the planner to create a unified district, without confining designers to a singular approach. By completing a comprehensive development plan containing design policies and regulations which outline the desired development, this neighborhood can become a dynamic transit district with a mix of retail, commercial and residential development to support a high quality of lifestyle with access to a wide variety of amenities close to downtown Kansas City.
Keywords: transit; district planning; Landscape Architecture (0390)